2013
DOI: 10.1038/ncomms2740
|View full text |Cite
|
Sign up to set email alerts
|

Basophils are required for the induction of Th2 immunity to haptens and peptide antigens

Abstract: The relative contributions of basophils and dendritic cells in Th2 skewing to foreign antigen exposure remain unclear. Here we report the ability of basophils to induce Th2 polarization upon epicutaneous sensitization with different antigens using basophil conditionally depleted Bas TRECK transgenic mice. Basophils are responsible for Th2 skewing to haptens and peptide antigens, but not protein antigens in vivo. Consistent with this, basophils cannot take up or process ovalbumin protein in significant quantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
147
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(156 citation statements)
references
References 31 publications
8
147
0
1
Order By: Relevance
“…It was shown that the transcription factors GLI1 and GLI2 activated the SOCS1 promoter, and STAT1 phosphorylation was reduced in cells with active Hh/GLI signaling (28). mRNA levels including IFNg depend on when the samples are collected (29,30). A previous report showed that IFNg mRNA expression in the skin-infiltrated IFNg-producing T cells increased at the peak of 12 hours and diminished after 24 hours in skin allergic inflammation (30).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the transcription factors GLI1 and GLI2 activated the SOCS1 promoter, and STAT1 phosphorylation was reduced in cells with active Hh/GLI signaling (28). mRNA levels including IFNg depend on when the samples are collected (29,30). A previous report showed that IFNg mRNA expression in the skin-infiltrated IFNg-producing T cells increased at the peak of 12 hours and diminished after 24 hours in skin allergic inflammation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Basophils alone were reported to polarize T cells towards Th2 for haptens and peptides antigens but needed the presence of DCs for protein antigens [18,19].…”
Section: Basophils and Th2 Cell Responsesmentioning
confidence: 99%
“…Of note, basophils reportedly express H-2M and invariant chain, which are key regulators of peptide loading on MHC-II, at very low levels compared with DCs, raising concerns about the basophil's antigen-processing and presentation ability (21). Moreover, the level of MHC-II expression on basophils varies, depending on experimental conditions, but it is generally much lower than that on professional APCs such as DCs and B cells (5)(6)(7)(8). Thus, the significance of MHC-II expression on basophils and the antigen-presentation capacity of basophils remain controversial (24).…”
mentioning
confidence: 99%
“…However, recent studies have revealed that basophils and mast cells play distinct roles in immune responses such as allergic inflammation and protective immunity to parasitic infections (2)(3)(4). Basophils also contribute to immune regulation through their interaction with other types of cells, including T cells (5)(6)(7)(8), monocytes (9,10), innate lymphoid cells (11), fibroblasts (12,13), and endothelial cells (14).…”
mentioning
confidence: 99%